PENERIMAAN PANELIS DAN ANALISIS USAHA MI INSTAN BERBASIS PATI SAGU DAN IKAN PATIN - Fitra Hardianti; Yusmarini '; Ahmad Rifai (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The purpose of this research was to analyze the panelist acceptance and business analysis of instant noodles based on sago starch and catfish (Pangasius sp). This research used 20 kilograms sago starch and catfish 3 kilogram. Instant noodles made from sago starch and catfish compared with commercial instant noodle (Indomie Goreng). Testing was conducted by giving an assessment toward taste, flavor, firmness, and texture. The assessment was conducted by 35 panelists. Panelist acceptance was tested for instant noodles before and after cooking. The panelist acceptance was analysed using Cohran's Q-test. Then do the business analysis of sago starch and catfish based-noodles, the code sample given 815 and 428. There were two different treatments (P), they are instant noodles sago starch and catfish-based before cooking, commercial instant noodles before cooking, instant noodles sago starch and catfish-based after cooking, and commercial instant noodles after cooking. Based on T-test for taste, firmness, and texture, there is a significant to instant noodles sago starch and catfish-based and no significant to commercial instant noodles, while the flavor of sago starch and catfish-based showed significantly different with commercial instant noodles. The conclusion of this study stated that the business analysis for instant noodle processing sago starch and catfish deserves to be marketed.   Keywords: Sago starch, instant noodle, catfish, panelist acceptance, analysis of business